PENGARUH COSTUMER EXPERIENCE DAN CUSTOMER BONDING TERHADAP DAYA SAING PADA KONSUMEN DI MEGA PARK MEDAN - Haloho, Elizabeth; Idamawati, Idamawati; Ginting, Maretta (Jurnal Manajemen dan Bisnis, 2023)
The purpose of this research is to find out and analyze customer experience which has a positive and significant effect on competitiveness, to know and analyze customer bonding which has a positive and significant effect on competitiveness, and to know and analyze customer experience and customer bonding which have a positive and significant effect simultaneously on competitiveness. to consumers in Mega Park Medan. The research method used is a quantitative descriptive research method. The population in this study were 96,000 consumers who had visited Mega Park Medan from January to June 2022. The technique for determining the sample in this study used Propotionate Stratified Random Sampling with a sample size of 100 respondents. The scale of data measurement in this study uses a Likert scale. The data analysis technique used is instrument test, classical assumption test, multiple linear regression analysis, hypothesis testing and coefficient of determination test (R2). The results showed that (1) the variable customer experience has a positive and significant effect on competitiveness, (2) the variable customer bonding has a positive and significant effect on competitiveness, and (3) the variable customer experience and customer bonding simultaneously has a positive and significant effect on competitiveness. Competitive with consumers in Mega Park Medan.